Multidisciplinarity in the Analysis of Jurisprudence (Docentes 2.0 Journal, 2013)
The syllogism is defined as that procedure carried out in order to “determine the truth or the falsity of the judgments, these must be expressed through affirmations and denials, which are the consequence and the result of the logical links established between them.” which must be represented in perfect reasoning, composed of two premises and a conclusion. But really, what is the true role of syllogism and logic in our profession as lawyers?
Keywords: Multidisciplinarity; Analysis of Jurisprudence